Selling Item that Have Not Been Paid in the Perspective of Mazhab of Syāfi‘iyyah and Ḥanābilah - Khaerul Aqbar; Azwar, Azwar; Ahmad Nurhadi Akkas (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research aims to determine the views of the Syāfi'iyyah and Ḥanābilah schools of thought regarding the status or validity of goods purchased on credit and the law of selling goods that have not been paid in full. This research is descriptive-qualitative (non-statistical) research, with the type of library research using normative and juridical-normative approaches. The results of the research show that the ownership status of goods that have not been paid for has been transferred (ownership) from the seller to the buyer, as indicated by the existence of a contract and the handover of both. This is part of the opinion of the Syāfi'iyyah and Ḥanābilah schools of thought. Selling goods that have not been paid off to the owner of the goods (lender), or what is known as 'īnah buying and selling, or to a third party (other than the first seller), is permissible in the view of the Syāfi'iyyah school of thought, provided that the buyer has received the object of the sale and purchase before he makes the next transaction. Meanwhile, in the view of the Ḥanābilah school of thought, selling goods that have not been paid for is permissible, but only if the purpose of purchasing the goods is to be used or traded properly, provided that the buyer has received the object of the sale and purchase before he carries out the next transaction.